A New Validated RP-HPLC Method for the Estimation of Darunavir Ethanolate in Bulk and Tablets (Asian Journal of Pharmaceutics (AJP), 2020)
Objective: Darunavir ethanolate is the last United States Food and Drug Administration approved proteaseinhibitor (PI). The drug is used along with other PIs (ritonavir/cobicistat) for the effective management ofhuman immunodeficiency virus (HIV) HIV-1 infection. Darunavir ethanolate exerts its action by binding noncompetitivelyto HIV protease enzyme. The main objective of the present research work was to develop a newprofound and novel reverse-phase high-performance liquid chromatography (RP-HPLC) for the estimation ofdarunavir ethanolate. Methods: As per the guidelines of the Food and Drug Administration and InternationalCouncil for harmonization, the method was validated. The HPLC analysis was performed on the waters 2695equipped with symmetry C18 column 3.5 μm, 150 mm × 4.6 mm, with a mixture of acetonitrile:0.1% phosphatebuffer (50:50 V/V) as the mobile phase, at the flow rate of 1 ml/min. The total run time was 5 min and thedetection was performed at the wavelength (λ) of 262 nm. Results: The retention time for darunavir ethanolatewas found to be 2.269 min. The standard curves were obtained with R2 0.9997 and linear at the concentrationrange of 8–120 μg/ml. The limit of quantitation and limit of detection for darunavir ethanolate were found tobe 0.08 μg/ml and 0.8 μg/ml, respectively. The method’s accuracy was tested by percentage recovery tests andfound to be 100.3%. The results obtained were within the accepted standards for linearity, accuracy, precision,specificity, and robustness. Conclusion: The proposed RP-HPLC method can be applied for the routine analyticalestimation of darunavir ethanolate in bulk and tablet formulations.